Analysis of the Integration Process of Vulnerable Communities in Social and Economic Development: Batwa Community of Muyange Site Two - Ndabarushimana, Alexis; Ndayizeye, Desire (European Scientific Journal, ESJ, 2024)
The lack of access to food, education, housing, medical healthcare, freedom of participation, and sanitary facilities are some characteristics of vulnerability. Vulnerability can arise from an individual, community, or larger population challenges, requiring diverse policy interventions from social and economic neighborhood development, and income policies, to individual medical support. Therefore, this study aims to analyze the integration process of vulnerable communities in social and economic development, specifically focusing on the Batwa community of Muyange Site Two. The study’s objectives are: (1) to identify the living conditions of the vulnerable Batwa communities in Muyange Site Two, (2) to highlight factors hindering the integration process in social and economic development, (3) to explore the role of local administration in integrating vulnerable communities, and (4) to propose practical solutions expediting the Batwa community’s integration. Employing stratified random sampling, the research included 50 households from a total of 200 households. It combined qualitative and quantitative methods, using interviews and questionnaires administered directly to the Batwa community. The study revealed challenges faced by the Batwa in accessing food, land for agriculture, and education, leading to extreme poverty. It also identified strategies for the Batwa, local administration, and the government to accelerate integration, emphasizing self-reliance and government support for housing and land ownership to overcome discrimination in the social and economic integration process.